MANAJEMEN KEUANGAN USAHA TEH DESA DALAM MENDUKUNG KEBERLANJUTAN USAHA - Rosmida Giawa; Enik Rahayu (LPPM STIE Muhammadiah Bandung, 2026)
Village tea enterprises are micro-scale businesses based on local potential that play an important role in supporting rural economic development. However, the sustainability of village tea enterprises still faces various challenges, particularly in financial management aspects. This study aims to describe and analyze financial management practices of village tea enterprises and their role in supporting business sustainability in Pringapus District, Semarang Regency. This research employs a qualitative approach with a case study design. The research subjects consist of village tea business owners who are directly involved in managing business finances. Data were collected through in-depth interviews, direct observation, and documentation, and analyzed using an interactive analysis model involving data reduction, data display, and conclusion drawing. The findings reveal that financial management practices of village tea enterprises remain simple and informal, characterized by basic cash-in and cash-out records, inconsistent separation between personal and business finances, and the absence of systematic financial planning. These conditions limit the ability of business owners to control cash flow and objectively evaluate financial performance. Nevertheless, the study finds that financial management plays a strategic role in supporting business sustainability, particularly in maintaining financial stability and guiding business decision-making. This study concludes that strengthening simple and contextual financial management practices is essential to support the long-term sustainability of village tea enterprises.